1299 Observational Study of The Use of Spinal Anaesthesia As an Alternative to General Anaesthetic For Ureteroscopy During The COVID-19 Pandemic. (12th October 2021) - Longshaw, A; Gallagher, W; Dickinson, A
Abstract: Introduction: General anaesthetic has traditionally been felt to be more appropriate than spinal anaesthesia for patients undergoing ureteroscopy as it is difficult to achieve a suitably high block. During the COVID-19 pandemic, our centre moved elective operating to an alternative day-case surgical environment where the anaesthetic team performed predominantly spinal anaesthesia and were therefore very experienced with this modality. In view of concerns of COVID-19 transmission by aerosolisation during the intubation and extubation phases of general anaesthetic, spinal anaesthesia as an alternative first line modality was trialled with the option of converting to general anaesthesia if surgery could not be achieved safely and comfortably for the patient. Method: During a three-month period, unless contraindicated, spinal anaesthesia was used as the first line anaesthetic for ureteroscopy cases. A retrospective study of outcomes was then undertaken. Results: 44 patients were treated with a conversion rate to general anaesthetic of 9% (n = 4). There was a complication rate of 20% (n = 9); 4 partial procedures, 4 readmissions with symptomatic residual fragments or sepsis and 1 patient required post-operative overnight stay due to anaesthetic. Spinal anaesthetic time averaged 25minutes. Conclusions: The global COVID-19 pandemic has led to change in practice and we have demonstrated that spinal anaesthesia is a valuable alternative to general anaesthetic in the majority of ureteroscopy cases. When undertaken by an experienced anaesthetic team, using this method does not significantly add to procedure time.